REALITAS VIRTUAL REALITAS SOSIOLOGI - Argyo Demartoto (Universitas Kristen Satya Wacana, 2013)
The rapidly communication technology development within the society correlates with the presence of change in a variety of life aspects including the computer-based interaction process having certain consequence. Internet technology serves as the social network media in cyberspace or virtual reality. Virtual reality apparently transforms the sociology subject matter from the real society into virtual society. The sociological studies shift from the conventional analysis units such as individual, household, community, and group to “mobile hybrid” side of virtual reality unit. For example, the one studying diaspora of minority ethnic through the study in their website, understanding the cultural transformation of internet mania community through their representation in cyberspace (virtual reality).Keywords : realitas virtual, transformasi, realitas sosiologi